THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE - Nurul Hikmatul Alawiyah; Yusniar Lubis; Fajar Rezeki Ananda Lubis (Journal of Information Systems Management and Digital Business, 2026)
Improving the performance of a state institution is inseparable from leadership and employee performance factors. The main objective of this study is to determine the effect of Transformational Leadership on the Performance of ASN Employees in the North Padang Lawas Regency Work Unit. The analytical method used in this study is Structural Equation Modeling (SEM) based on SmartPLS. The study population is ASN Employees in the North Padang Lawas Regency Work Unit. Sampling was carried out by selecting a portion of the population so that the results of the analysis can be used to draw conclusions that apply to the entire population. The sampling technique used is cluster random sampling, and the calculation of the number of samples uses the Slovin formula, so that 369 samples were selected proportionally. The Effect of Transformational Leadership on Employee Performance. The analysis shows that Transformational Leadership has a positive effect on employee performance with a coefficient of 0.241, a t-statistic of 2.829, and a p-value of 0.005. The results of the study indicate that there is an influence of Transformational Leadership on Employee Performance. So it can be said that Transformational Leadership is very important to be implemented in the North Padang Lawas Regency Work Unit. This study found that Transformational Leadership is a part that can make employees more enthusiastic about working.